Pengaruh Nilai Perusahaan, Ukuran Perusahaan, dan Profitabilitas terhadap Pengungkapan Environmental, Social, and Governance (ESG) pada Perusahaan Sektor Keuangan Terdaftar di BEI : Studi pada BBCA dan BBRI Periode 2021–2023 - Jais Rahmawati; Aris Eddy Sarwono (Pusat Riset dan Inovasi Nasional, 2025)
This investigation aims to analyze the effect of firm value, firm size, and profitability on Environmental, Social, and Governance (ESG) disclosure in financial companies on the Indonesia Stock Exchange, especially BBCA and BBRI, for the period 2021–2023. Based on the results of multiple linear regression analysis that meet the classical hypothesis, it was found that the three independent variables did not have a significant effect on the ESG Score either partially or simultaneously, indicated by the significance value (p>.05) in the t and F tests. These results indicate that internal financial variables such as firm value, size, and profitability cannot provide an adequate explanation for the variation in the level of ESG disclosure in the banking companies studied, so further research is needed by considering other variables, such as external factors, regulatory pressure, or reputation strategy, to understand the determinants of ESG disclosure more comprehensively in the context of the financial sector in Indonesia.